Management of stormwater pollution using green infrastructure: The role of rain gardens. (6th January 2021) - Sharma, Rozi; Malaviya, Piyush
Abstract: Major modifications are needed in existing stormwater management practices to control floods in urban landscapes, protect natural ecosystems, and minimize infrastructural destruction due to stormwater hazards. Stormwater management combined with urban design can be the best solution to minimize urban flooding risks and promote a clean natural environment. Green infrastructure (GI) is an environmentally sustainable alternative to traditional methods of stormwater management. Rain gardens, a GI, play a vital role in reducing rainwater volume and flow, prevent asset's destruction, remove pollutants from urban runoff, and recharge groundwater. Rain gardens can remove sediments, heavy metals, pathogens, nutrients, hydrocarbons from stormwater via several mechanisms. Various amendments in soil media help in delayed saturation, low sorption capacity, limited pollutant mobility, and bioaccumulation/biotransformation of metals/organic compounds in rain gardens. Soil media and plants play a vital role in the pollutant removal processes of rain gardens. Various plant‐based mechanisms and chemical processes like adsorption, reduction, sedimentation, cation‐exchange capacity, complexation, and so forth are involved in the removal of contaminants from stormwater. Construction and design considerations; different models of rain gardens; working mechanisms; performance assessment tools like capacity tests and synthetic runoff tests; removal of stormwater pollutants, and biphasic rain gardens have been critically discussed in this review. The state‐of‐the‐art review approaches to provide fundamental knowledge of rain gardens and in‐depth analyzes its potential as a stormwater management tool. Future directions on improving efficiencies of rain gardens have also been discussed for prospective researchers. This article is categorized under: Engineering Water Abstract : This state‐of‐the‐art advanced review delivers fundamental knowledge about rain gardens, their construction and design considerations, contaminant removal mechanisms, hydraulic performance assessment tools, various modifications, and analyzes their potential as a nature‐based solution for stormwater management in the urban ecosystem.